2017
DOI: 10.1097/jpo.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Transtibial Prosthetic Alignment Quality and Step-by-Step Variance of Gait

Abstract: Introduction The quality of lower-limb prosthetic alignment cannot easily be measured directly but may be described by its effects on gait comfort and efficiency. It is known that gait stability and step variability are correlated, as are gait stability and prosthetic alignment. This study investigated the hypothesis that prosthetic alignment and step variability are correlated. This would have the implication that step variability can be measured to assess the quality of prosthetic alignment (and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…This may indicate that the perceived accommodation quality increased along time and exercise. A similar finding was reported on the effect of prosthetic alignment, which was reflected both in measureable gait variables and in users' perceptions [26].…”
Section: Discussionsupporting
confidence: 82%
“…This may indicate that the perceived accommodation quality increased along time and exercise. A similar finding was reported on the effect of prosthetic alignment, which was reflected both in measureable gait variables and in users' perceptions [26].…”
Section: Discussionsupporting
confidence: 82%
“…The sagittal prosthetic foot or shoe alignment was changed in six studies. 4,17,18,22,29,31 The sagittal socket alignment was changed in one study. 28 The effect of sagittal and frontal prosthetic alignment adjustments were analyzed in 12 studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, step-by-step variability showed weak correlation to these variables. 4 Kobayashi et al analyzed out-of-plane and in-plane effects of improper alignment on forces and moments at base of the socket (referred as socket reaction moment) in six studies. They found that both angular and translational changes have some significant out-of-plane and in-plane effects (Table 3).…”
Section: Not Specifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjective verification of an experienced prosthetist regarding lack of gait deviation, along with subjective feedback of an active and experienced prosthetic user is the clinical gold standard for acceptable alignment assessment (D. A. Boone et al, 2012;Fiedler & Johnson, 2017). The results of proposed method revealed no report of gait deviation and the quality of prosthetic alignment was evaluated highly favorably by the patient.…”
Section: (B) Feasibility Of Anatomical-based Prosthetic Alignment Methodsmentioning
confidence: 99%